Cardiovascular Toxicity Induced by Chronic Vincristine Treatment - Herradón, Esperanza; González, Cristina; González, Antonio; Uranga, Jose Antonio; López-Miranda, Visitación (Frontiers in Pharmacology, 2021)
Vincristine is an effective anticancer agent for treating leukemias, lymphomas, and other solid tumors. Vincristine’s better-known severe side effects include bone marrow depression, hyponatremia, peripheral neuropathy, and gastrointestinal distress. In recent years, cardiovascular damage also has been described during vincristine treatments. However, the vascular toxicity induced by vincristine is little studied. The aim of the present is to evaluate whether these alterations remain after the suspension of chemotherapy treatment (sequelae) and the possible mechanisms involved in this vascular damage. Adult male Wistar rats were used. The animals were divided into four treatment groups: two groups of saline (0.9% NaCl; saline, sequelae saline) and two groups of vincristine (100 μg/kg; vincristine, sequelae vincristine). Saline or vincristine was administered intraperitoneally in two cycles of 5 days each, leaving a rest period between cycles of 2 days. The final cumulative vincristine dose administered was 1 mg/kg. Sequelae groups correspond to 2 weeks after stopping treatment with the antitumor agent. At the end of the different experimental protocols, cardiac and vascular functions were analyzed. Alterations in the expression of different proteins in the cardiovascular tissues were also investigated. Chronic treatment with vincristine did not produce significant changes in basal cardiac function but provoked significant endothelial dysfunction in the aorta and a significant decrease in the mesenteric contractile function. These cardiovascular functional alterations disappeared 2 weeks after the suspension of chemotherapy treatment. Vincristine treatment caused a significant increase in the expression of tumor necrosis factor-alpha (TNFα), endothelial and inducible nitric oxide synthases (eNOS and iNOS), and connexin 43 in cardiac tissue. In the aorta, the chronic treatment with vincristine caused a slight non-significant increase in TNFα expression, a significant increase in eNOS and iNOS, and a significant decrease in connexin 43. After 2 weeks of vincristine treatment (sequelae group), the expression of TNFα increased and eNOS and iNOS expressions disappeared, but a significant decrease in the expression of connexin 43 was still observed in the aorta. In mesenteric arteries, similar data to those found in the aorta were observed. In conclusion, chronic treatment with vincristine causes functional alterations in the vascular function of both conductance and resistance vessels and changes in the expressions of TNFα, eNOS, iNOS, and connexin 43 in cardiovascular tissues, implicating direct toxicity during its treatment. These functional alterations are transitory and disappear after the suspension of its treatment.